Psychosocial predictors of drug involvement among secondary school students (2016)
"Predictors of drug involvement among secondary school students in Ibadan were examined in this study. Two hundred and four (204) students comprising 113 males and 91 females, whose age ranged between 13 and 25 years (M = 16.32, S.D. = 1.81) participated in the study. Data collected with a structured questionnaire were subjected to independent sample t-test, and regression analysis. Psychosocial factors (life purpose, need for achievement and self-esteem) significantly predicted drug abuse [F (6, 113) = 7.75; p < .01, R2 = .29]. Participants with low score on life purpose reported higher substance abuse than those with high score on life purpose, t (161) = 2.62, p <.05 ; those with low score on the need for achievement reported higher substance abuse than those with high score on the need for achievement, t (162) = 4.09, p < .01 ; those with low score on the need for achievement reported higher substance abuse than those with high score on the need for achievement t (162) = 2.62, p <.05; female participants reported higher substance abuse than male counterparts, t (176) = - 4.05, p <.01). In conclusion, it is expedient that efforts be intensified on actions that will reawaken the strive for excellence and sense of self worth through engagement in self development activities, thereby minimizing the prevalence of substance abuse among Nigerian youths."